Participation Motives for High School Students on Physical Education School Championship in Greece - Goltsos, Κωνσταντίνος; Soulas, Δημήτριος; Tzika, Δροσιά; Goudas, Μάριος; Theodorakis, Γιάννης (Inquiries in Physical Education and Sport, 2011)
The course of physical education in high school carries out an important role since it simultaneously cultivates the body and the spirit of students as well. The school championships of physical education are part of the course of physical education. The aim of the present study was to examine the motives that encourage the high school students to participate in school championships in Greece. The participants were 2535 high school students aged 15-18 (1182 male and 1353 female). In order to evaluate the motives a questionnaire was used, (Γκόλτσος & Κουθούρης, 2005). It was realised that the most important motives for the students were the "self-control/skill development" and the "relaxation/escape". Results of the MANOVA for gender, sport club, class and residence revealed that boys have more motives of "excitement/self projection" and "achievement/social recognition" than the girls. The participation of students in sport clubs is an important motive for them so that they participate in the school championship. The students of smaller classes seek more motives of "achievement and social recognition" contrary to the students the C class who seek motives of "self-control and skills development". Finally the students that reside in urban regions look more for relaxation and escape from the everyday routine and also the self-control and the skills development process in relation to the students of other regions. The re-designing of school championships, has been proposed aiming at a more recreative character and also at a higher participation of students.